Chitosan‐capped silver nanoparticles: A comprehensive study of polymer molecular weight effect on the reaction kinetic, physicochemical properties, and synergetic antibacterial potential. (4th February 2022) - Kulikouskaya, Viktoryia; Hileuskaya, Kseniya; Kraskouski, Aliaksandr; Kozerozhets, Irina; Stepanova, Elena; Kuzminski, Ivan; You, Lijun; Agabekov, Vladimir
Abstract: The search for novel efficient antibacterial agents is attracting a great attention due to the unregulated use of common antibiotics and development of multidrug‐resistant bacteria strains. This paper proposes an eco‐friendly approach to obtain stable chitosan‐capped silver nanoparticles with controlled physicochemical and biological properties using reducing and stabilizing capacity of chitosan. The study of the influence of chitosan characteristics on the kinetic of Ag + reduction showed that an increase in polysaccharide molecular weight led to a decrease in their reducing ability. The synthesized silver nanoparticles were characterized by UV and FTIR spectroscopy, TEM, XRD, DLS. The relationships between physicochemical characteristics of the formed silver nanoparticles and the type of used chitosan, as well as synthesis temperature, were determined. It has been demonstrated that spherically‐shaped (13–27 nm) and positively‐charged (zeta‐potential 26.1–29.5 mV) silver nanoparticles with a single symmetric SPR band at 408–418 nm are stable during 6 months in a colloidal form, and can be produced with the assistance of low‐molecular weight chitosan (20–30 kDa) at 95°C. The synthesized silver nanoparticles enhanced the antibacterial activity of kanamycin and ampicillin against both gram‐negative and gram‐positive bacteria. These results revealed the prospects for the application of chitosan‐capped silver nanoparticles to create new effective antibacterial systems (gels, films, etc). Abstract :